2015
DOI: 10.1111/infa.12096
|View full text |Cite
|
Sign up to set email alerts
|

The Quality of Spontaneous Movements of Preterm Infants: Associations with the Quality of Mother–Infant Interaction

Abstract: The assessment of the quality of infants’ spontaneous movements is a diagnostic tool for the young nervous system. We examined whether it relates to the quality of the interactions between infants born preterm and their mothers. Thirty‐nine healthy infants born preterm (Mage in weeks = 14.59, SD = 2.21; 38.46% female) and their mothers participated in the study. Infants’ quality of spontaneous movements was assessed using the General Movement Assessment according to Prechtl (Prechtl, Early Human Development 19… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 84 publications
1
8
0
Order By: Relevance
“…A previous study showed that the quality of infants’ early motor repertoire might explain some of the variability in the interactions between preterm-born infants and their mothers. (25) It might be that smooth and fluent movements on the part of the infant lead to another type of parent-child interaction than non-fluent movements. It is known that language development already starts early on in life.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study showed that the quality of infants’ early motor repertoire might explain some of the variability in the interactions between preterm-born infants and their mothers. (25) It might be that smooth and fluent movements on the part of the infant lead to another type of parent-child interaction than non-fluent movements. It is known that language development already starts early on in life.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, infants who display smooth and fluent movements engage more easily with their mother. 19 To sum up, infants with normal FMs are very likely to show a neurologically normal development. This is irrespective Fidgety movements S67 of pre-or perinatal complications and is therefore vital for their parents' comfort.…”
Section: Normal Fmsmentioning
confidence: 99%
“…We investigated the association between infants' spontaneous movement and the attunement of the mother-infant interaction in a pilot study of a small sample of infants born preterm at the CA of 3-4 months (Lev-Enacab et al, 2015). We found the continual expression of FMs was associated with more sensitive maternal touch and holding.…”
Section: Mother-infant Interactionsmentioning
confidence: 96%
“…Sixty Israeli mothers and their preterm-born infants participated in this study. Thirty-nine of these dyads participated in our pilot study (Lev-Enacab et al, 2015). Dyads were recruited via flyers in NICUs and pediatric clinics, and electronic flyers were published on social networks sites for mothers of infants.…”
Section: Participantsmentioning
confidence: 99%
See 1 more Smart Citation